Five-year relative survival by stage of breast and colon cancers in northern Italy - Mangone, Lucia; Marinelli, Francesco; Bisceglia, Isabella; Braghiroli, Maria Barbara; Damato, Angela; Pinto, Carmine (Frontiers in Oncology, 2022)
The aim of this study is to present the 5-year relative survival by stage of breast and colorectal cancer patients in a northern Italian province. For the period 2013-2015, cases were selected from the Reggio Emilia Cancer Registry. Breast cancer patients were divided into 3 age groups: <45, 45-74 (the target screening population) and 74+. Colorectal cancers patients were classified into <50, 50-69 (the target screening population), and over 69 years. Carcinomas in situ and unknown stage were both excluded from the survival analyses. The five-year relative survival was estimated using the Pohar Perme method. During the period examined, 1,450 breast cancers and 992 colorectal cancer cases were registered. Analyzing in detail the patients with breast cancer for the entire 2013-2015 period, we noted that 50.4% were in stage I, 33.6% in stage II, 10.8% in stage III and 3.8% in stage IV. The stage was unknown in only 1.3% of patients (19 cases). The stage data of patients with colorectal cancer showed 24.5% were in stage I, 26.1% in stage II, 23.4% in stage III, and 24.6% in stage IV, and 1.4% unknown. Breast cancer 5-year survival was 100%, 89.7%, 71.4%, and 29.1% for stages I, II, III and IV, respectively and for colon cancer 96.7%, 83.4%, 70.8% and 16.2%, respectively.The presence of cancer screening, associated with effective treatments, account for the high survival rate of early-stage breast and colon cancers.